Estudos ecológicos em taxocenoses helmínticas de Chaunus ictericus (Spix, 1824) e C. schneideri (Werner, 1894) (Anura: Bufonidae) simpátricos, capturados no distrito de São Cristóvão, Município de Três Barras, Santa Catarina. - Hoppe, Estevam G Lux; Pedrassani, Daniela; Hoffmann-Inocente, Ana Cecília; Tebaldi, José H; Storti, Luis Fernando; Zanuzzo, Felipe S; Avancini, Neuri; Do Nascimento, Adjair Antonio (My University, 2008)
Fifty eight Chaunus ictericus and 42 C. schneideri specimens were collected on São Cristóvão district, Três Barras, SC for helminthological studies. Fourteen helminth species were diagnosed, from which only five species were found on both hosts. Chaunus ictericus showed higher values of species richness (2,8448+/-1,1516) and diversity (H = 1,374), with mild dominance (1-D = 0,642, J = 0,5528), in comparison with C. schneideri (0,6428+/-1,007; H = 1,165; 1-D = 0,5822 e J = 0,5985). Also, descriptors of helminthic infection were superior in the former host. Little number of shared species between the analyzed toad species suggests parasitic host-specificity.
Ecological studies on helminthic taxocenosis of sympatric Chaunus ictericus (Spix, 1824) and Chaunus schneideri (Werner, 1894) (Anura: Bufonidae) captured on São Cristóvão district, Três Barras county, Santa Catarina State, Brazil
Keywords: animal; Brazil; helminth; isolation and purification; parasitology; toad; Animals; Bufonidae; Helminths